AN INVESTIGATION INTO SYNTACTIC, SEMANTIC AND PRAGMATIC FEATURES OF WISHES IN ENGLISH AND VIETNAMESE - Nguyễn Thị Cẩm Vân (Trường Đại học Ngoại ngữ, 2025)
This study makes an effort to deal with a part of wishes: the semantic, syntactic and pragmatic features of wishes in English and Vietnamese. The collection of samples has been taken from websites, films, videos in both languages. The analysis is carried out to find out similarities and differences in syntactic, semantic and pragmatic fields of English and Vietnamese wishes. The thesis also suggests some implications for teaching and learning of the second language in particular.